Local‐Time and Vertical Characteristics of Quasi‐6‐Day Oscillation in the Ionosphere During the 2019 Antarctic Sudden Stratospheric Warming. Issue 21 (30th October 2020) - Lin, J. T.; Lin, C. H.; Rajesh, P. K.; Yue, Jia; Lin, C. Y.; Matsuo, T.
Abstract: This study investigates new characteristics of ionospheric modulations driven by quasi‐6‐day wave (Q6DW) burst following a rare Antarctic sudden stratospheric warming (SSW) in September 2019. Local‐time and vertical variations of the amplitude and phase of quasi‐6‐day oscillation (Q6DO) in the ionosphere are examined by using data assimilation analysis of electron density from three‐dimensional Global Ionosphere Specification (GIS). The maximum amplitudes of Q6DO are located symmetrically ±20° off the magnetic equator at ~12 LT, with a secondary peak at 17 LT. The amplitude of Q6DO weakens at 15 LT, with a sudden phase shift, suggesting multiple dynamo processes driving the Q6DO‐related ionospheric variations. The altitude‐latitude structure of Q6DO shows that the ionospheric modulations extend beyond the equatorial ionization anomaly, indicating the wind dynamo source regions at higher latitudes. A likely physical mechanism is discussed based on possible interactions of Q6DW and semidiurnal migrating tides leading to the dynamo modulation and phase differences. Plain Language Summary: Sudden stratospheric warming (SSW) is an extreme meteorological phenomenon in the polar stratosphere, which usually occurs in the Northern Hemisphere. Numerous studies have shown that the SSW can significantly disturb the entire atmosphere from the troposphere all the way to the upper thermosphere and ionosphere. In September 2019, a rare and record‐breaking SSW occurred in the Antarctic region, providing an opportunity to investigate the ionospheric variabilities connected to the Antarctic SSW, which is seldom explored. In this study, we present observations of the time evolution and vertical structure of quasi‐6‐day oscillation (Q6DO) in the ionosphere generated from the unusually large quasi‐6‐day wave (Q6DW) in the mesosphere and lower thermosphere. Our results show that the observed Q6DO behavior in the ionosphere is quite different from climatological characteristics in the local time and vertical structure, which indicates that the coupling mechanisms driving the ionospheric variability are complex due to the presence of Antarctic SSW. Key Points: Local time and vertical structures of the quasi‐6‐day oscillation (Q6DO) in the global ionosphere during the 2019 Antarctic SSW are examined Unlike the climatological Q6DO that peaks only at 16 LT, the Q6DO peaks at 12 LT and 17 LT during this sudden stratospheric warming (SSW) Longitude shift of the two Q6DO peaks implies more than one quasi‐6‐day wave related perturbations are competing in the dynamo process